2017
DOI: 10.1093/icvts/ivx046
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral circulation estimated by laser speckle flowgraphy in retrograde femoral arterial perfusion during minimally invasive cardiac surgery

Abstract: clinicaltrials.gov : 15102-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…32 LSFG was also used as a neuromonitor of cerebral circulation for retrograde femoral artery perfusion. 33 In our wound assessment, the relative flow volume significantly increased in the perimeter and centre of the wounds after 2 weeks, and all wounds improved by washing with a natural soap containing fatty acid salts. Cleansing with fatty acid salts may aid in wound bed preparation by reducing the infectious biological burden.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…32 LSFG was also used as a neuromonitor of cerebral circulation for retrograde femoral artery perfusion. 33 In our wound assessment, the relative flow volume significantly increased in the perimeter and centre of the wounds after 2 weeks, and all wounds improved by washing with a natural soap containing fatty acid salts. Cleansing with fatty acid salts may aid in wound bed preparation by reducing the infectious biological burden.…”
Section: Discussionmentioning
confidence: 60%
“… 32 LSFG was also used as a neuromonitor of cerebral circulation for retrograde femoral artery perfusion. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Our group reported previously that LSFG is useful for measuring optic nerve head flow during minimally invasive cardiac surgery with retrograde femoral arterial perfusion. 5 Moreover, we indicated that mean blur rate measured by LSFG may correlate with findings of near-infrared spectroscopy during both retrograde and antegrade cerebral perfusion under hypothermic circulatory arrest. 6 In this present case, LSFG was able to detect the ocular perfusion qualitatively and quantitatively in a critically ill patient undergoing central ECMO and IABP.…”
Section: Intra-aortic Balloon Pump Does Not Impede Cerebral Microcircmentioning
confidence: 53%
“…LSFG is considered a promising tool for perioperative neuromonitoring in cardiovascular surgery. 1,[5][6][7] We measured cerebral microcirculation using LSFG in a clinical setting. Our group reported previously that LSFG is useful for measuring optic nerve head flow during minimally invasive cardiac surgery with retrograde femoral arterial perfusion.…”
Section: Intra-aortic Balloon Pump Does Not Impede Cerebral Microcircmentioning
confidence: 99%